Urbanização do Lazer: Reflexões sobre Produção e Consumo da Paisagem em Cidades Turísticas - Silva, Maria da Glória Lanei da (Paisagem e Ambiente, 1999)
Tourism is the world's largest grow th business in the last decades, besides telecommunications and information science. In Brazil, we can observe this im provement in the increase of trips, in touristic service options, in job creation (new opportunities and careers, including third level courses) and in the public and private investments in means of transportation and hotel system.The urban space in general is affected by this new economic arrangement in many ways, such as the physical and morfological transform ation or changes in the population social-economic level. In touristic cities, however, this process is notable. In fact, the tourism (re)build another city in that places.This paper presents reflections on the relationship between work, capital and leisure in the governmental experience of touristic planning in Bahia, focusing the urban landscape. The tourism is an im portant piece in built environment process and we discussactions that treat it like sustainable development agent, one of the basic concepts in public policies and economy during these days